Interpersonal Intelligence as a Predictor of Ensemble Music Learning Outcomes among Senior High School Students - Nino Sadewo; Nafik Salafiyah; Rasheed Adeyinka Uthman (Program Studi Pendidikan Musik FBS UNP, 2025)
Objective: This study aims to analyze the influence of interpersonal intelligence on students’ learning outcomes in music education, particularly in ensemble learning, among Grade XI students at SMA Negeri 2 Sragen. Interpersonal intelligence is regarded as an essential ability in collaborative music learning, which requires cooperation, communication, and coordination among students. Method: This study employed a quantitative approach with a correlational research design. The participants consisted of 36 Grade XI students at SMA Negeri 2 Sragen. Data were collected through an interpersonal intelligence questionnaire, observations of ensemble learning activities, supporting interviews, and documentation of students’ learning outcomes. The data were analyzed using simple linear regression to determine the extent of the influence of interpersonal intelligence on music learning outcomes. Results and Discussion: The results of the analysis revealed a significance value of 0.000 (p < 0.05), indicating a significant influence of interpersonal intelligence on ensemble music learning outcomes. The coefficient of determination (R²) of 0.589 shows that interpersonal intelligence contributed 58.9% to the variance in students’ music learning outcomes. These findings suggest that students with higher interpersonal intelligence tend to collaborate more effectively, communicate more efficiently, and adjust their roles within ensemble groups, resulting in more optimal musical performances. Conclusion: Interpersonal intelligence has a significant influence on music learning outcomes in ensemble-based learning. Therefore, the development of interpersonal intelligence should be emphasized in collaborative music learning strategies to enhance students’ learning outcomes and the quality of social interaction in music education.